2013
DOI: 10.1016/j.resp.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of plasma copeptin: A systematic investigation in a pediatric mechanical ventilation model

Abstract: Copeptin, the C-terminal part of the arginine vasopressin precursor peptide, holds promise as a diagnostic and prognostic plasma biomarker in various acute clinical conditions. Factors influencing copeptin response in the critical care setting are only partially established and have not been investigated systematically. Using an in vivo infant ventilation model (Wistar rats, 14 days old), we studied the influence of commonly occurring stressors in critically ill children. In unstressed ventilated rats basal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
2
20
1
Order By: Relevance
“…This result with copeptin is most likely explained by very recent observations that just a few contractions (most likely acting via transient periods of minor hypoxia on the fetus) are sufficient to trigger detectable AVP/copeptin [24]. Given the cumulative nature of the copeptin levels with a half-life of 30 min [25], the above dependence on labor duration is readily explained. Thus, future work on sequential measurements of copeptin may turn out to be valuable in enhancing the prognostic power of this biomarker.…”
Section: Discussionmentioning
confidence: 95%
“…This result with copeptin is most likely explained by very recent observations that just a few contractions (most likely acting via transient periods of minor hypoxia on the fetus) are sufficient to trigger detectable AVP/copeptin [24]. Given the cumulative nature of the copeptin levels with a half-life of 30 min [25], the above dependence on labor duration is readily explained. Thus, future work on sequential measurements of copeptin may turn out to be valuable in enhancing the prognostic power of this biomarker.…”
Section: Discussionmentioning
confidence: 95%
“…Blood sampling and blood gas analyses were performed as described by L'Abate et al. (). Blood was withdrawn by direct cardiac puncture after a partial laparotomy and sternotomy before disconnection from the ventilator.…”
Section: Methodsmentioning
confidence: 99%
“…The animal experiments were performed between February and July 2011. The protocols for animal preparation, allocation to study groups, and MV were reported previously (L'Abate et al 2013). Briefly, at the day of the experiment, anesthesia was induced with inhalative isoflurane followed by an intraperitoneal (IP) injection of ketamine (75 lg/g body weight, BW) and xylazine (12 lg/g BW) solution.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations